Development of Canva Animated Videos in Science and Social lessons for IV Grade Students at Muhammadiyah Bumiayu Elementary School - Siti Khoeriyah; Suprapto Yuni; Anwar Ardani; Diyah Ayu Retnoningsih (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2026)
This research is motivated by the lack of student activity and low average scores in IPAS lessons, which is 59.64. Based on the data from 28 students, 8 students scored above 70 and the rest scored below the Minimum Passing Grade. This research aims to develop Canva-based animated video learning media to improve student activity and learning outcomes in 4th-grade IPAS lessons at SD Muhammadiyah Bumiayu. This type of research is Research and Development (R&D) research using the ADDIE method (Analyze, Design, Develop, Implement, Evaluate). Data collection techniques used observation, interviews, questionnaires, and documentation. The product was tested by media experts, content experts, language experts, and IPAS learning experts and was declared highly suitable for use, achieving an average percentage of 90.8%. In the response test stage, 28 students gave a very good response with an average percentage result of 92.5% for the Canva-based animated video media. Based on the research results, it can be concluded that this Canva-based animated video media is declared highly suitable for use as a learning medium.